ANALISIS STRUKTUR TUBUH TERHADAP KETERAMPILAN BERMAIN SEPAKTAKRAW PADA ATLIT SEPAKTAKRAW KABUPATEN BANGGAI - MUHAMMAD SALAHUDDIN (JURNAL PENDIDIKAN GLASSER, 2017)
AbstractThe reseach aims to discover the description of the body strukture, the physical ability and sepaktakraw skill, as well as to determine the correlation between body structure toward sepaktakraw skill, the correlatioan between the physical ability toward sepaktakraw skill of the athletes Kabupaten Banggai.This study was adescriptive correlation study with two independent variables, namely the body structure and the physical as well as the dependent variable which the sepaktakraw skill. Yhe study populatioans were male athlete of sepaktakraw Kabupaten Banggai by number of sample of 30 people which was taken through random sampling technique.Based of the result of the reseach, it can be summarised that : (1) body structure of sepaktakraw athletes Kabupaten Banggai is classified in fair category where 3 people classified as very good, 3 people classified as good, 9 people were classified as fair, 8 people were classified as poor, 7 people were classified as very poor; (2) Sepaktakraw skill of the athletes Kabupaten Banggai is classified as good, where 8 person was classified as excellent, 11 people were classifiedas good, 8 people were classified as fair, 2 people were classified as poor, and 1 people were classified as very poor; (3) there is significant correlation between the body strukture toward the athletes skill Kabupaten Banggai. It is obtained by calculating the correlation (ro) = 0.656 (P < 0.05);.Keywords: Body structure, Sepaktakraw skill